Can urban environmental problems be overcome? The case of Skopje—world’s most polluted city - Arsovski, Slobodan; Kwiatkowski, Michał; Lewandowska, Aleksandra; Jordanova Peshevska, Dimitrinka; Sofeska, Emilija; Dymitrow, Mirek (Bulletin of Geography. Socio-economic Series, 2018)
The condition of the environment is one of the most fundamental concerns of cities worldwide, especially when high levels of pollution and environmental destruction exert immense impact on people’s quality of life. This paper focuses on Skopje, the capital of Macedonia, which often tops the charts as the world’s most polluted city. Despite associated problems such as congestion, ill health, and premature death, Macedonia’s scarce resources are instead spent on controversial projects, such as ’Skopje 2014’, involving creating a national identity through massive and extremely costly constructions of neo-classical government buildings, museums and monuments. The aim of this paper is to compare the situation of Skopje to environmentally oriented activities conducted in several Polish cities and to discuss the possibility of their implementation in Skopje. Considering the scale and scope of Skopje’s environmental problems, the paper offers some priorities for action, including solutions that emphasize institution building, technical input and self-governance. It also highlights a number of economic, ecological, and socio-cultural contradictions involved in the process of achieving sustainable development.